A comparison between acute large vessel occlusion in the posterior circulation and anterior circulation after endovascular treatment: the ANGEL-ACT registry experience. Issue 4 (8th March 2022) - Sun, Xuan; Zhang, Jingyu; Tong, Xu; Jia, Baixue; Mo, Dapeng; Ma, Ning; Gao, Feng; Liu, Lian; Huo, Xiaochuan; Song, Ligang; Deng, Yiming; Miao, Zhongrong
Abstract : Background and purpose: Endovascular treatment (EVT) has shown an overwhelming benefit for acute anterior circulation artery occlusion (ACO). Whether it can achieve the same outcomes in posterior circulation artery occlusion (PCO) has not been well explained. We aimed to evaluate the characteristics and prognosis of ACO and PCO after EVT in a nationwide registry. Method: The present analysis was based on the prospective ANGEL-ACT Registry in China between November 2017 and March 2019. Demographic data, periprocedural times, recanalisation rate, intracranial haemorrhage (ICH) and 90-day functional outcomes were compared between the ACO and PCO groups. Results: A total of 1793 patients were analysed including 397 (22.1%) consecutive patients with PCO and 1396 (77.9%) patients with ACO treated with EVT. A larger proportion of patients with PCO had intracranial atherosclerotic disease and received extra angioplasty during EVT. Successful recanalisation and 90-day favourable functional outcomes did not differ significantly between the two groups. Patients with PCO showed lower 24-hour ICH and symptomatic ICH rates. There was a trend towards higher mortality rate in the PCO group (22.09% vs 14.44%; adjusted OR 1.286 (95% CI 0.820 to 2.017), p=0.2731), especially when the onset to puncture time was over 6 hours (30.77% vs 11.13%; adjusted OR 2.673 (95% CI 1.280 to 5.583), p=0.0089, interactive p=0.0002). Conclusions: In this large prospective multicentre registry, there was a significant difference in the characteristics and periprocedural features between patients with PCO and ACO. However, successful recanalisation and 90-day favourable functional outcomes in PCO were equivalent to those in ACO.